PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS V DI MI AL-FALAH
Education will evolve continuously following the times. As human beings who have creative and innovative potential will surely follow the development of an increasingly advanced era in order not to be left behind. Every teacher is expected to have skills in teaching one of them is to choose a learning model so that learning can be conveyed interestingly. The purpose of this research is to know the students ’ learning Achievement in social studies subjects (IPS